High-rate sputtering deposition of high- and low-refractive index films from conductive composites. (21st May 2015) - Zhou, Li Qin; Fan, Qi Hua; Simões, Raul; Neto, Victor
Abstract: Abstract : Dielectric thin films of high- and low-refractive index are the essential components for optical coatings. To achieve high sputtering rates and superior film quality, the authors have developed novel conductive SiO2 :Si and ZnO:Zn composites that become conductive once the doped silicon and metal Zn reach a critical ratio. The sputtering characteristics of the composite targets in direct current and radio-frequency (RF) plasma discharge are quite different from the corresponding element targets. The optical properties of the RF sputtered SiO2 and ZnO films from the composite targets is comparable with the films obtained from RF sputtering of pure oxide targets.